THE GOLGI COMPLEX IN LIVING OSTEOBLASTS - Rose, George G. (The Rockefeller University Press, 1961)
Embryo chick leg bones were cultivated under sheets of dialysis cellophane in multipurpose culture chambers. The osteoblasts emigrating in this environment contained phase gray juxtanuclear bodies from which phase white droplets emanated. These were concluded to be the Golgi complex and are described with respect to their living morphology, microscopically observed functional activity, vital staining, and cytochemical reactions.